In vivo and in vitro evaluation of the efficacy of cypermethrin high-cis (ECOTOMIN) against economically important cattle ticks in Ethiopia - Mekonnen, S.; Kgasi, A.; Mureithi, W.; Zena, G.; Tekle, T.; Gebre, S.; Jobre, Y.; Bryson, N.R. (2004)
From November 2003 to March 2004, a field trial was conducted to evaluate the efficacy of the synthetic pyrethroid cypermethin high-cis formulation (Ecotomin 100 EC - Novartis AH) against economically important cattle ticks in Ethiopia. An In Vitro oviposition response of engorged female Boophilus decoloratus after immersion in Ectomin was also evaluated. Twenty crossbred cattle, naturally infested with Amblyomma variegatum, B. decoloratus, Hyalomma marginatum rufipes and Rhipicephalus evertsi evertsi, were used in the In Vivo trial. Based These experimental cattle, aged between 1-5 years and weighing 150-400kg, were randomly allocated into two groups The first group (n=10) was hand sprayed with freshly prepared Ectomin emulsion at the recommended dilution. The second group (n=10) served as an untreated control. Adult ticks were collected from all animals, counted and identified in situ and percentage control achieved as a result of the application of the test acaricide (Ecotomin) was calculated. There was a significant difference (p<0.05) in mean tick counts between the groups throughout the trial period. Rapid tick-kill effect was observed after a day post-treatment (91% tick control). Between day 6 and 22, 100% tick control was achieved. The overall efficacy of a single Ectomin application was 98%. At the term of the trial, tick counts in the control animals was low, a finding attributable to the rub-off effect of Ectomin. The latter finding also suggests that the residual effect of Ectomin is longer than what is normally expected. The findings from the in vitro oviposition response of engorged female B. decoloratus after immersion in Ectomin revealed that almost all treated ticks were unable to lay eggs. The results of the present study strongly suggest that Ectomin 100 EC may be applied at 21 days intervals and provide effective protection against the economically important cattle ticks in Ethiopia.